External peak demands are not affected by playing venue (home vs away) during official male basketball games - Perez-Chao, E. A.; Trapero, J.; Ribas, C.; Sosa, C.; Gomez, M. A.; Lorenzo, A. (International Journal of Performance Analysis in Sport, 2023)
Aim: To quantify and compare the external peak demands (PDs) encountered according to team`s venue (home vs. away) in under-18 years (U18), male basketball players. Methods: 12 basketball players had external load variables monitored across 16 official games using inertial movement units (IMUs). PDs were calculated across 1-min and 5-min time windows for PlayerLoad™ (PL). Linear mixed models for repeated measures were used to compare PDs for PL according to playing venue (home vs. away). Results: Regarding 1- and 5-min time windows, no significant differences (p > 0.05, small effect size) were apparent between playing venues. Conclusions: External PDs remain consistent (small effects) regardless of playing venue in U18, male basketball players. Accordingly, playing venue may not be a key determinant of external PD attained during official games.